Ethnolinguistics Study of Street Name Toponyms in Sesela Village Mountain Sari, West Lombok (e-Journal of Linguistics, 2026)
This study aims to examine the toponymy of street names in Sesela Village, Gunungsari District, West Lombok Regency, by analyzing their forms, meanings, and cultural values. This study uses a qualitative descriptive method with an ethnolinguistic approach. Data were obtained through observation, interviews with community and traditional leaders, and historical document analysis. Data analysis was conducted using an ethnosemantic approach and cultural interpretation. The results of the study show that the toponymy of street names in Sesela Village consists of only two categories, namely naming based on social figures and historical events. The novelty of this study lies in the finding that street naming is completely dominated by social and historical memory, without involving geographical or natural aspects, thus confirming the function of toponymy as a medium for preserving collective memory and strengthening the cultural identity of the local community.